2008
DOI: 10.1007/s00208-008-0265-9
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the unit root along the Dwork family of Calabi–Yau varieties

Abstract: We study the variation of the unit roots of members of the Dwork families of Calabi-Yau varieties over a finite field by the method of Dwork-Katz and also from the point of view of formal group laws. A p-adic analytic formula for the unit roots away from the Hasse locus is obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…, j. For the Apery sequence (case b) this was also conjectured in [22]. (It follows from [10] that A, B, C, D satisfy the Dwork congruences).…”
Section: Namementioning
confidence: 56%
See 1 more Smart Citation
“…, j. For the Apery sequence (case b) this was also conjectured in [22]. (It follows from [10] that A, B, C, D satisfy the Dwork congruences).…”
Section: Namementioning
confidence: 56%
“…(see [8,13,20,22] 1. An F -crystal over W (k) is a free W (k)-module H of finite rank with a σ-linear endomorphism…”
Section: Dwork Unit-root Crystalsmentioning
confidence: 99%
“…The first half of the theorem follows from Lemma 2.2.1 because a ≡ F 1,1 (λ −α ) (mod p). The proof of the second half goes exactly as in [Yu,p.76,proof of Theorem 4.3 (2)].…”
Section: Preliminaries On Hypergeometric Functionsmentioning
confidence: 91%
“…In turn, they related the other nontrivial factors of Z(X ψ , T ) to the action of discrete scaling symmetries of the Dwork pencil F 5 on homogeneous monomials. In related work (but in a somewhat different direction), Jeng-Daw Yu [Yu08] showed that the unique unit root for the middle-dimensional factor of the zeta function for the Dwork family in dimension n can be expressed in terms of a ratio of holomorphic solutions of a hypergeometric Picard-Fuchs equation (evaluated at certain values).…”
Section: Introductionmentioning
confidence: 99%